A knowledge transfer programme: Peers for Youth Engagement & Reachable Support (PYERS) / Nur Afiqah Ab. Latif... [et al.] - Ab. Latif, Nur Afiqah; Adnan, Nur Ilianis; Affendy Lee, Noor Azli; Abdul Halim, Muhammad Aiman (Academy of Language Studies, 2022)
The English Language Club of UiTM Cawangan Pulau Pinang (UiTMCPP) collaborated with Kolej Komuniti Seberang Jaya to organise a community service online mentorship programme - Peers for Youth Engagement & Reachable Support (PYERS). The programme was conducted via WhatsApp and Google Meet from October 18, 2021, to December 3, 2021. The PYERS programme aims to encourage and guide students who are weaker in the English language to enhance their communication skills. Led by some of the executive members of the club who are UiTMCPP diploma students from the Permatang Pauh campus, the programme committee also consisted of students from other UiTM campuses such as Bertam and Melaka who were also interested in the project. Under the guidance of UiTM English language lecturers, eight committee members participated as the facilitating mentors in this programme, while the students of Kolej Komuniti participated as the mentees.